Genetic Distances in Two Gracilaria Species (Gracilariaceae, Rhodophyta) Identified by PCR Technique - Kim, Young Sik (Dev Reprod, 2018)
Genomic DNA was isolated from the Gracilaria vermiculophylla (GRV) and G. chorda (GRC) from Jangheung located in the southern sea of the Korean Peninsula, respectively and we performed clustering analyses, DNA polymorphisms and the genetic differences. The seven selected primers OPC-01, OPA-04, OPA-05, OPD-07, OPD-08, OPB-10, and OPD-16 generated average bandsharing (BS) value, the genetic distance and dendrogram. The size of DNA bands varies from 90 bp to 2,400 bp. The average BS value was 0.859±0.004 within GRV and 0.916±0.006 within GRC. The average BS value between two Gracilaria species was 0.340±0.003, ranged from 0.250 to 0.415. The dendrogram obtained by the seven primers, indicates two genetic clusters. The genetic distance between two Gracilaria species ranged from 0.059 to 0.513. The individual VERMICULOPHYLLA no. 07 of GRV was genetically closely related to VERMICULOPHYLLA no. 06 of GRV (genetic distance=0.059). Especially, two entities between the individual VERMICULOPHYLLA no. 10 of GRV and CHORDA no. 22 of GRC showed the longest genetic distance (0.513) in comparison with other individuals used. Accordingly, as mentioned above, PCR analysis showed that the GRV was a little more genetically diverse than the GRC species. We convinced that this DNA analysis revealed a significant genetic distance between two Gracilaria species pairs (p<0.01).